Optimasi Produktivitas Alat Berat dengan Metode Simpleks LINGO (Heavy-Duty Productivity Optimization Using LINGO Simplex Method) - Heru Setiyo Cahyono; Apif Miptahul Hajji; Aisyah Larasati; Imam Alfianto (Universitas Tribhuwana Tunggadewi Malang, 2022)
One of the areas that are now the location for clearing residential land is in Karang Widoro Village, which is now a plantation and fruit farm and has been purchased by the developer Podo Joyo Masyhur (PJM) Group who then runs the project